The Intrapersonal Communication Model of Parents with Autistic Children in Tangerang - Rahman, Farah Shalsabila; Destiwati, Rita (Jurnal Ilmu Komunikasi, 2022)
Autism Spectrum Disorder (ASD) is a developmental disability that can cause significant social, communication, and behavioral challenges. Having a child with ASD is an exceedingly important challenge for parents. Parents must deal with their child's repetitive behavior, difficulties with speech, understanding, and uncontrollable tantrums. Parents had to face financial problems regarding the high cost of nurturing their children and the high intensity of negative stigma in the surrounding environment. This situation has not fully received the attention and care of the surrounding community. This study aims to explain and discover the intrapersonal communication model among parents with autistic children in Tangerang. This study uses a descriptive qualitative method with data collection techniques, namely observation and unstructured interviews. Six parents in Tangerang city were selected using purposive sampling. Through four stages, the results of this research show that the intrapersonal communication of parents with autistic children is represented as sad, disappointment, anger, confusion, scared, traumatized, self-acceptance, self-approach to God, treatment attempts, etcetera. This research is conducted to support parents with autistic children to increase their confidence in raising their children. This research also contributes information and education to the public regarding the intrapersonal communication of parents with autistic children.